The Boundaries of Russian Identity Analysis of the Concept of Russkiy Mir in Contemporary Russian Online Media - Kozdra, MichaÅ‚ (Lingua Cultura, 2018)
This article set out to present selected outcomes of my research on the concept of â€œrusskiy mirâ€ in contemporary ethnocentricÂ online Russian media. Perspectives for further analysis were also presented. The analytical methodology involved a semanticÂ and cultural analysis of a dataset from a cognitive and anthropological viewpoint including elements of critical discourseanalysis. The concept of â€œrusskiy mirâ€ in the ethnocentric discourse investigated in this article was based on an idea ofÂ forming a supranational Russian civilization. This community would unite all Russians, the Russian diaspora and all thoseÂ learning Russia, and declaring the attachment to Russian culture. Proponents of this discourse assume that â€œrusskiy mirâ€ willÂ have a geopolitical dimension, imperial pretenses and will transgress state borders, and claiming for itself a transcontinentalÂ realm. A nationality dimension is also supposed to be an important aspect according to the discourse participants. The mainÂ ethnos is to be that of the Russian nation, around which other ethnoses will congregate. The Orthodox religion is supposedÂ to be an important co-constituent of â€œrusskiy mirâ€.